APPLICATION OF INNOVATIVE STRATEGIES IN EDUCATION IN THE PROCESS OF DIGITAL TECHNOLOGIES - I. N. Khaitova (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes and analyzes the features of developing a strategy for introducing digital technologies and modern methods into the educational process in Uzbekistan. The structure of the activities of the country's communication networks and its analysis in a narrow and wide range is carried out. There are proposals for the development of the introduction of digital technologies and modern methods in the educational process in Uzbekistan.